THE EVOLUTION OF EDUCATIONAL MARKETING - Manea, Natalia; PURCARU, Mihaela (Annals of Spiru Haret University. Economic Series, 2017)
The association of the term ‘educational’ to the term ‘marketing’ generates a specialized domain, by applying methods, politics and marketing strategies in the area of education. Due to the cultural, social and complex role of the education, educational marketing represents a part of the services marketing, the social marketing and the non-profit organizations. By offering mandatory educational services, financed from the state budget, the school units, through their activity, respect the principles of social marketing, regardless of the financial benefits that result from the provision of these services. This article aims to place educational marketing below the conceptual level in the field of service marketing; the reference works in the field of educational marketing are not many, a consequence of the fact that this is a new field.